2008
DOI: 10.1038/sj.tpj.6500486
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen synthase kinase-3β gene is associated with antidepressant treatment response in Chinese major depressive disorder

Abstract: Evidence suggests that glycogen synthase kinase-3b (GSK3B) activity is increased significantly in the brain of patients with major depressive disorders (MDD). Inhibition of GSK3B is thought to be a key feature in the therapeutic mechanism of antidepressants. To investigate whether common genetic variants in the GSK3B gene are associated with MDD and the therapeutic response to antidepressants, four polymorphisms (rs334558 (À50 T4C), rs13321783 (IVS7 þ 9227 A4G), rs2319398 (IVS7 þ 11660 G4T) and rs6808874 (IVS1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
2
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 21 publications
1
32
2
2
Order By: Relevance
“…This polymorphism is likely to be associated with antidepressant response, as suggested by a study in bipolar depressed patients treated with total sleep deprivation where the TT homozygote showed better response [147]. In contrast to these results, other investigations reported that the C allele resulted in favorable variant [148,149].…”
Section: Crisafulli C Et Al: Pharmacogenetics Of Antidepressant Drugcontrasting
confidence: 45%
“…This polymorphism is likely to be associated with antidepressant response, as suggested by a study in bipolar depressed patients treated with total sleep deprivation where the TT homozygote showed better response [147]. In contrast to these results, other investigations reported that the C allele resulted in favorable variant [148,149].…”
Section: Crisafulli C Et Al: Pharmacogenetics Of Antidepressant Drugcontrasting
confidence: 45%
“…Among those, we found Slc7a10 (also known as Asc-1; r ¼ 0.81), which is involved in controlling hyperexcitability (Xie et al, 2005). Almost all significant probe sets were negatively correlated with theta activity and belong to cluster 5, such as Narg1l (r ¼ À0.91), Dnajb14 (Hsp40) (r ¼ À0.82), and Gsk3b (r ¼ À0.81), a cell-proliferation gene associated with antidepressant treatment response (Tsai et al, 2008). It should be noted that the EEG measurements for theta and beta-2 activity were negatively correlated (r ¼ À0.64), and thus probe sets that correlated with one tended to show an opposite correlation with the other.…”
Section: Phenotype-gene Expression Correlationsmentioning
confidence: 96%
“…In a recent study, Tsai et al (2008) recruited 230 Chinese MDD patients and also found no significant association of MDD with the alleles and genotypes of single locus or fourlocus haplotypes (rs334558, rs13321783, rs2319398, and rs6808874). However, three of the four polymorphisms investigated were significantly associated with an antidepressant therapeutic effect ( p = 0.002-0.011).…”
Section: Discussionmentioning
confidence: 99%
“…Lithium, a mood stabilizer that enhances the action of antidepressants, was found to inhibit GSK3b in vitro, in the mouse brain (Klein and Melton, 1996;Stambolic et al, 1996) and in human peripheral blood mononuclear cells (Li et al, 2007). Furthermore, Tsai et al (2008) have reported an association between genetic variation in GSK3b and response to 4 weeks of selective serotonin reuptake inhibitor antidepressant therapy in Chinese individuals with MDD.…”
mentioning
confidence: 99%
See 1 more Smart Citation